Pelatihan Konten Digital untuk Promosi Wisata Lokal di Desa Gunung Tugel Probolinggo - Muhammad Ali; Deny Alfan Humaidi (Yayasan Literasi Altruis Khatulistiwa, 2025)
Gunung Tugel Village in Bantaran District, Probolinggo Regency, has tourism potential that has not been fully utilized. One of the main problems faced is the low skills of the community in promoting local tourist destinations, which results in a lack of attractiveness for tourists. In ord er to enhance the village's tourism potential, this service program is designed to provide digital content creation training to the local community. This training includes an introduction to the basics of photography, videography, and digital marketing strategies that aim to improve the community's ability to promote tourist attractions independently through online platforms. The solution offered is to increase the community's capacity in producing creative and effective content to attract tourists. Thus, this training is expected to be the first step in developing the village economy through the tourism sector. In conclusion, through this community empowerment-based tourism activation, it is hoped that Gunung Tugel Village can become a more recognized and desirable tourist destination, which in turn will have a positive impact on the welfare of the local community